EFFECT OF EXTERNAL FACTORS ON PURCHASE DECISIONMAKING IN “NUVO” THE SHOWER SOAP (A Case Study in District Consumer Mlati, Sleman regency, Yogyakarta) - Andri, Andri (Accounting, 2010)
Basically, the products offered by producers and consumers purchased, is the expected demand. Therefore, consumers will choose goods or services that can meet the expectations. Consumers as a target marketing company´s products, always decide what he wants to be bought and consumed. According to Private Companies and Handoko (1997:10), consumer behavior can be defined as the activities of individuals who are directly involved in obtaining and using goods and services, including decision-making process on the preparation and determination of these activities. It is interesting in this research is in the purchase decision of consumers to maintain healthy body soap. Consumer considerations in choosing products more diverse and often influenced by factors outside themselves (external) the culture surrounding communities, social factors, personal factors and the existence of the family (Simamora Bilson, 2003; 4-12). Keywords: Consumers, Decision Making, Society